(untitled) (Editora Impacto Científico, 2025)
This work had the goal of monitoring the internal and external weather conditions of a greenhouse at CEFET/RN school, Brazil. The experiment was carried out to evaluate the efficiency of mulch in retaining the soil humidity, and decreasing the temperature on the soil surface through the measuring records of temperature and relative humidity in both environments. Moreover, the rate of evaporation inside and outside the greenhouse was determined by the measurement of the loss of water mass in Class A evaporation pans. The monitoring for these parameters took place from November 4 to December 11, 2005. The use of the protection for the soil with dry leaves showed a reduction on the rate of the soil evapotranspiration (p<0,01). DOI: https://doi.org/10.56238/edimpacto2025.090-018